Faculty of physical culture of zabsu: development of sports in the trans-baikal territory - Kuznetsov V.V.; Yaremchuk O.A.; Pryazhennikova M.V. (Theory and Practice of Physical Culture, 2025)
Abstract The article celebrates the 65th anniversary of the Faculty of Physical Culture and Sports at Zabaikalsky State University (ZabSU), which has a rich history deeply intertwined with the advancement of physical culture and sports in the Trans-Baikal region. Objective of the study was to examine the significance of the Faculty of Physical Culture and Sports at ZabSU as a driving force in the advancement of sports culture in the Trans-Baikal region through a historical lens. Methods and structure of the study. In the course of our research, we have compiled a comprehensive collection of all-Union and national legal documents related to physical culture and sports, as well as reporting materials from the archives of the Trans-Baikal Territory State Archive. These documents provide a detailed account of the activities of the Faculty of Physical Culture and Sports at the Trans-Baikal State University. We have then analyzed and compared the information extracted from these documents. Results and conclusions. Throughout the history of the faculty, it has been a hub for the training of essential professionals, including physical education teachers, coaches, sports event organizers, and, of course, individuals who contribute to the success of sports. Furthermore, the article highlights that the Faculty of Physical Culture and Sports at ZabSU has consistently been a driving force behind the organization of sports events at the city, regional, national, and international levels, some of which have become established traditions. The article also emphasizes the importance of this department within the university in the context of evolving regulations that reflect the advancement of physical culture and sports in our country. The authors conclude that the Faculty of Physical Culture and Sports at the university continues to serve as a leading training ground for the field of physical culture and sports in the Trans-Baikal region and beyond.